On the neutral gas content of nine new Milky Way satellite galaxy candidates. Issue 1 (13th August 2015) - Westmeier, T.; Staveley-Smith, L.; Calabretta, M.; Jurek, R.; Koribalski, B. S.; Meyer, M.; Popping, A.; Wong, O. I.
Abstract : We use a new, improved version of the H i Parkes All-Sky Survey to search for H i emission from nine new, ultrafaint Milky Way satellite galaxy candidates recently discovered in data from the Dark Energy Survey. None of the candidates is detected in H i, implying upper limits for their H i masses of typically several hundred to a few thousand solar masses. The resulting upper limits on $M_{\rm H\small {I}} / L_{\rm V}$ and $M_{\rm H\small {I}} / M_{\star }$ suggest that at least some of the new galaxy candidates are H i deficient. This finding is consistent with the general H i deficiency of satellite galaxies located within the Milky Way's virial radius and supports the hypothesis that gas is being removed from satellites by tidal and ram-pressure forces during perigalactic passages. In addition, some of the objects may be embedded in, and interacting with, the extended neutral and ionized gas filaments of the Magellanic Stream.